Hubungan Pemberian Asi Eksklusif Dengan Perkembangan Motorik Halus Pada Balita Usia 3 Sampai 5 Tahun - Emi Wulandari (2018)
ABSTRACT Exclusive breastfeeding is only giving breast milk for 6 months without providing any food or drink. Exclusive breastfeeding can help the process of growth and development of children to achieve optimal maturity of one of them smooth motor development. The purpose of this study was to determine the relationship of exclusive breastfeeding with the development of fine motor in children aged 3-5 years.This type of research is correlational analytic, using analytical survey research design. Population as many as 32 respondents and 32 samples of respondents using saturated sampling technique. The independent variable is exclusive breastfeeding. Dependent variable is the development of fine motor. To analyze the relationship of exclusive breastfeeding with gross motor development of PAUD students 3-5 years used Mann Whitney Test. The results showed that respondents who gave exclusive breastfeeding and smooth motor development according to 24 respondents (75%), Exclusive breastfeeding with the development of fine motor doubted there are 2 respondents (6.2%), while respondents who do not provide exclusive breastfeeding with development Fine motor according to there are 3 respondents (9,4%) and which is not given exclusive breastfeeding with the development of fine motor doubted there are 3 respondents (9,4%). From the results of analysis using Mann Whitney test obtained asymp results. Sig. (2-tailed) = 0.011 which means there is a relationship between exclusive breastfeeding with the development of fine motor in children aged 3-5 years in PAUD Sabilillah Village Tanjung District Kertosono Nganjuk 2017 with a strong relation ship level. Based on the above description can be concluded that exclusive breastfeeding affects the development of fine motor. It is hoped that the research site will detect early incidence of fine motor development which is not suitable with SDIDTK monitoring every 3 months, and provide counseling for respondent's parents to give exclusive breastfeeding and stimulate children as early as possible in accordance with the stage of development.